The analysis of loads and results of experimental research of load-bearing systems of overhead travelling rail cranes = Analiza obciążeń i wyników badań doświadczalnych układów nośnych suwnic natorowych - Matysiak, Antoni; Grochowska, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the analysis of the influence of standard shifts in crane loads on a supportive structure. It has been shown that the valid standards' conditions were established without carrying out suitable tests. The presented results of the experimental research have not confirmed the standards in terms of the occurrence of forces.
Keywords: dźwignica; obciążenia; suwnica natorowa; badania doświadczalne; crane; load; industrial objects; experimental research